Analysis of Factors Affecting Fintech Consumers in Indonesia - Gilang Pratama Hafiz; Dodi Ria Atmaja; Fachmi Tamzil (Universitas Mercu Buana, 2023)
The researcher conducted a pre-survey in order to find out more about the reasons that make consumers choose digital payment providers in making daily payments. From the pre-survey that was asked of 100 consumers, it was found that there were 4 factors that dominated the determination of consumer intentions in choosing digital payment providers. Based on the situation analysis and pre-survey findings, it is important to conduct this research so that it can become a strong theoretical foundation for stakeholders in the financial technology industry (FINTECH) in Indonesia and can contribute to the success of government programs in encouraging the development of the digital economy and digitalization in Indonesia. The sample involved 1,713 respondents with certain criteria and was analyzed using the structural equation modeling method. The findings state that the intention to use FINTECH can be increased through user satisfaction. Customer satisfaction is strongly influenced by the diffusion of innovation from the technology presented in the service, where the service must be able to make it easier for users to transact. Customer satisfaction must be a priority in designing customer-oriented product and service management, so as to form brand integrity that reflects quality service. To obtain a better determination, especially in assessing customer satisfaction using mobile payments, many factors such as Hedonic Value, Information Quality are factors that are suspected to have antecedents that need to be tested.